1989
DOI: 10.1007/bf00257626
|View full text |Cite
|
Sign up to set email alerts
|

Severe renal toxicity due to intermediate-dose methotrexate

Abstract: Methotrexate (MTX) is a drug widely used in the treatment of patients with malignant disease. Its well-known side effects include myelosuppression, mucositis and renal damage. These problems are primarily dose-related, tending to occur more frequently when high doses (greater than 1 g/m2) are given. We present four cases in whom severe renal and mucosal toxicity occurred with intermediate doses (200 mg/m2) of MTX despite folinic acid rescue. Possible reasons for this occurrence are discussed and means of avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 8 publications
0
18
2
Order By: Relevance
“…Although it has been reported that MTX also has negative effects on the excretion of CEX into the urine by glomerular filtration and tubular secretion, 22,23 there were no significant differences in the terminal elimination rate constant (Ke) among the different groups in the present study (data not shown) because NaHCO3 was used to minimize the adverse effects of MTX on kidney function. Cephalexin is a hydrophilic ionic compound that is largely absorbed from the small intestine via the active transporter PEPT1 and it is metabolized very little.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although it has been reported that MTX also has negative effects on the excretion of CEX into the urine by glomerular filtration and tubular secretion, 22,23 there were no significant differences in the terminal elimination rate constant (Ke) among the different groups in the present study (data not shown) because NaHCO3 was used to minimize the adverse effects of MTX on kidney function. Cephalexin is a hydrophilic ionic compound that is largely absorbed from the small intestine via the active transporter PEPT1 and it is metabolized very little.…”
Section: Discussioncontrasting
confidence: 56%
“…Cephalexin is a hydrophilic ionic compound that is largely absorbed from the small intestine via the active transporter PEPT1 and it is metabolized very little. Although it has been reported that MTX also has negative effects on the excretion of CEX into the urine by glomerular filtration and tubular secretion, 22,23 there were no significant differences in the terminal elimination rate constant (Ke) among the different groups in the present study (data not shown) because NaHCO3 was used to minimize the adverse effects of MTX on kidney function. Changes in the Cmax and AUCCEX observed in MTX-treated rats could be explained as the result of functional changes in the intestinal absorption of CEX by carrier-mediated transport systems and/or passive diffusion through the tight junction.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, if too little LV is given it can lead to the MTX associated toxicities. Although LV administration is based on the individual’s clearance of MTX, there are still reports of toxicity and death in patients receiving HDMTX 19-21. These studies imply that earlier commencement and an increase in the amount of LV given could have prevented these toxicities and fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…Resulting sustained and elevated plasma concentration causes a marked enhancement of MTX's other toxicities. 5 Thus, finding a nephroprotective agent is mandatory for the safe use of this important drug. Heat-shock proteins (HSPs) are highly conserved and ubiquitously expressed molecular chaperones that help restore normal cellular function following an injury.…”
Section: Introductionmentioning
confidence: 99%